The Zombi/e Diaspora: Urban Manifestations and Dany Laferrière’s Pays Sans Chapeau - Ruthven, Andrea (Revista (Entre Parênteses), 2017)
Zombies are not new additions to our cultural horror imaginary, and yet it would seem that in recent years their presence has become even more pervasive. Where they might once have been confined to the cinematic or literary monsters that drool and stagger their way across our screens and through our texts, the capitalist, globalised landscape has become populated with these creatures. They have come to occupy urban landscapes, whether in the form of protesters at the various Occupy movements throughout the West in the autumn of 2011, through advertising campaigns or the popular ‘zombie walks.’ Their presence in our cities is curious and problematic, as the contemporary zombie is an adaptation of the Haitian Voodoo zombi, which is itself of West African traditions. The scope of this article is less to trace the ontological origins of the zombie than it is to question the possible implications of its re-appropriation in North American and globalised landscapes coming, as it does, from the Haïtian representation of both slave and slave rebellion. As a way of focusing this exploration of zombie lore, the present article will turn to Dany Laferrière’s novel Pays Sans Chapeau (1996) [Down Among the Dead Men, 1997]. Laferrière’s own migration, as an exile and immigrant, from Port-au-Prince to Montreal to Miami, informs this semi-autobiographical novel in which he returns to Haiti after 20 years abroad and encounters a landscape full of zombies. By teasing out the meaning of the beings Laferrière finds when he returns to his home, and their possible relationship to the monsters present in North American culture, this paper will come to a better understanding of the metamorphosis of the zombie in its travels from West African tradition through the Caribbean and into the nightmares of contemporary consumers.